THE MEASURENMENT OF ELECTRICITY AND DIELECTRIC CHARACTERISTIC OF ONION (ALLIUM CEPA) - Abd Wahidin Nuayi; Farly Reynol Tumimomor (Universitas Negeri Gorontalo, 2019)
This experiment aimed to measurenment of the electricity and dielectric characteristic of onion (Allium cepa). In this study, the onion have been done through the variation of frequency and temperature. The frequency was setup in 30 different values from 100 Hz -1 MHz with the temperature are from 26 0 C up to 40 0C with each increase of 2 0C. The measurement was performed on AC current in 1 kHz and input voltage is one volt. The ions through to the membrane was measured as a conductance value by using LCRmeter that connected with two pieces of AgCl electrodes on both side of the membrane. Beside that, the conductance (G) was measured by the variation temperature of the solution. The results based on the electric characteristics variation of the frequency shows that the electricity of the onion membrane from the conductance itself is tend to increase and the capacitance is decrease due to increasing of the frequency. However, the conductance and the capacitance of the soaked onion membrane is increase doe to increase of the temperature than the original onion membrane. In adddition, the increasing of conductance to temperature was plotted on ln G to 1/T curve. The slope or gradient of the curve is used to determine the change of the self-energy of the membrane and its pore radius. Self-energy of ion which obtained from non-washed and washed and soaked (with distilled water) membrane is respectively 7,66967 x 10-21 J or 0,04787 eV dan 1,2156 x 10-19 J or 0,7869 eV ( 1 joule = 6,2415 x 1018 eV) and the average of pore membrane radius is 2,00 x 10-9 meter (2,00 nm) and 1,26 10-10 meter (0,126 nm). Based on the results the onion membrane could be a good membrane for established the electrisity anf the dielectricity.